(untitled) (Journal of the College of Basic Education, 2022)
bacterial isolates collected from children patients with urinary tract infections in the age of under 5 years. Was obtained on 72 isolation of the bacterium Escherichia coli and the number of males 49 isolated females and the number is 61 bacterial isolates were Altejes using microscopic tests and bio - chemical, and tested the sensitivity of isolates to antibiotics in accordance with the method (Kerby Bauer) where isolates showed a high degree of sensitivity to antibiotics, Impenem where The resistance ratio (0% (and anti Pipracillin the resistance ratio (100%) while the resistance of bacteria to anti Ceftazidime ratio of 100% and resistance to anti-gentamycin and by 68.5% and resistance to anti Meropenem increased by 98.6% and counter-counter-Amikacin the percentage of resistance 81.9% and anti Ampicillin was resistance 100% and anti Trimethoprim rate was the proportion of resistance 83.3% and anti Aztreoname the resistance ratio 72.22% Tobramycin the percentage of resistance is 70.8%, and used the 72 bacterial isolates to detect the gene for virulence factor Fim (H), and the expression of isolates for virulence Fim factor (H) 100% where the PCR method was used to detect the presence of the gene in isolates intended